Immunonutrition as a potential strategy to prevent and cope with coronavirus disease (COVID-19) - Acevedo-Espinola, R. (2022)
In this article, a brief review of immunonutrition as a feasible alternative to modulating the immune system in defence of the SARS-CoV-2 that causes COVID-19 was presented. Immunonutrition is the nutritional practice that includes the necessary nutrients to modulate the activity of the immune system in health and disease. To date, studies are encouraging because they indicate that a good diet restores or improves the immune system's response to pathogens such as SARS-CoV-2. In addition, applying immunonutrition helps people recover with fewer sequelae after going through a serious infection in hospitalization and/or intensive care unit. Finally, it is suggested that immunonutrition be applied in conjunction with other good lifestyles and strictly following current health recommendations.